DESKRIPSI RESPONS SISWA KELAS X SMA NEGERI 1 PEMANGKAT TERHADAP MEDIA KOMIK PADA MATERI VIRUS - Tawila, Ila; Panjaitan, Ruqiah Ganda Putri; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out the suitability of comic on virus material as teaching media and find out the responses of Class X High School students to comic on virus material. The study is a descriptive study with survey method. The subjects in this study are 101 students of Class X MIA in SMA Negeri 1 Pemangkat. The instrument used to measure the suitability of comic is validation sheet, while to measure the students’ responses by using questionnaire. The validity tests are conducted by 7 validators. The aspects that measured for the suitability of comic are including physical,design, colours, material, pictures and writings aspect. While the criterias for students’ responses are response and reaction. In the response criteria it consist of format and relevantion indicators. Reaction criteria consist of interest, satisfaction and confidence indicators. From the result of comic validation it acquired the value of CVR and CVI 0,99 for all the measured aspects, this value shows that comic is suitable to be used as teaching media. The results of questionnaire analysis obtained the mean value of students’ responses is 83,63% with positive response category shows that the students are giving positive responses to comic on virus material. Keyword: Students’ Responses, Comic, Virus Material